Microsatellite Evolution in The Yeast Genome - A Genomic Approach - Merkel, Angelika (University of Canterbury. School of Biological Sciences, 2010)
Microsatellites are short (1-6bp long) highly polymorphic tandem repeats, found in all genomes analyzed so far. Popular genetic markers for many applications including population genetics, pedigree analysis, genetic mapping and linkage analysis, some microsatellites also can cause a variety of human neurodegenerative diseases and may act as agents of adaptive evolution through the regulation of gene expression. As a consequence of these diverse uses and functions, the mutational and evolutionary dynamics of microsatellite sequences have gained much attention in recent years. Mostly, the focus of studies investigating microsatellite evolution has been to develop more refined evolutionary models for estimating parameters such as genetic distance or linkage disequilibrium. However, there is an incentive in using our understanding of the evolutionary processes that affect these sequences to examine the functional implications of microsatellite evolution. What has emerged from nearly two decades of study are highly complex mutational dynamics, with mutation rates varying across species, loci and alleles, and a multitude of potential influences on these rates, most of which are not yet fully understood.